A new non-entangled quantum secret sharing protocol among different nodes in further quantum networks - Fu, Si-Jia; Zhang, Ke-Jia; Zhang, Long; Hou, Kun-Chi (Frontiers in Physics, 2022)
As an important branch of quantum secure multi-party computation, quantum secret sharing (QSS) can distribute secret information among dishonest network nodes without revealing the secrets. In this study, a new four-party QSS protocol based on locally indistinguishable orthogonal product (LIOP) states is first proposed for quantum network communication. Then, the general multiparty QSS model based on LIOP states will be expanded. Combined with the property of LIOP states and obfuscating operation, the source node can send the secrets to different destination nodes in the quantum network. Accordingly, it is proven that the destination nodes have to work together to recover the shared secrets against some existing attacks. Furthermore, no entangled resources and complicated operations are required in the presented protocol. We hope the results could make positive effects to the development of quantum secure communication in the future.